Training on the Use and Utilization of Google Site for SMAN 3 North Luwu - Muhammad Akram Hamzah; Siaulhak Siaulhak; Selni Ranggina; Dasril Dasril (Yayasan Cendekiawan Digital Indonesia, 2024)
In today's technological development, the role of the internet is increasing rapidly and will continue to increase in the future, one of which is the website. Creating a website requires effort and learning with a long time, especially for people who are unfamiliar with the world of technology. Therefore, to simplify the process of creating a website, one of the facilities that can be utilized is that we can use the Google site which is one of the features of Google. However, not everyone knows the facilities or features contained in the Google site. In fact, almost all SMA Negeri 3 North Luwu students do not know this feature. The purpose of this community service is training on the use of Google Site for SMA Negeri 3 North Luwu students. This activity was attended by 29 students using lecture and hands-on practice methods. The material and practices carried out include the introduction, utilization and creation of google sites.